BAHASA ARAB SEBAGAI KEKHASAN PESANTREN DAN TANTANGANNYA DALAM SITUASI GLOBAL - Mohammad Makinuddin (JP : JURNAL PENDIDIKAN, 2017)
This article discussed Arabic as pesantren feature and its challenges in global situation. Pesantren and Arabic are inseparable. Arabic was taught in any pesantren, at least in grammatical aspects and passive Arabic development, this can be seen in which learning kitab kuning that used Arabic is necessity. In order to get the purpose, Arabic grammatical learning is also become a part of developed curriculum structure. Thus, in the context of globalization, the study of kitab kuning and Arabic script is essential for someone’s existence, and competitive in this increasingly globalized era. In addition, the study of science in global era requires language mastery especially Arabic. So the position of pesantren in that context becomes a very strategic place to develop Arabic in order to face up the challenges in global situation.Key words: Pesantren, Arabic, Global Situation